Four Partners, Three‐Step, One‐Pot Reaction for a Library of New 2‐Alkyl(dialkyl)aminoquinazolin‐4(3H)‐ones. (1st May 2014) - Caruso, Anna; Lancelot, Jean‐Charles; El‐Kashef, Hussein; Panno, Antonella; Sinicropi, Maria Stefania; Legay, Rémi; Lesnard, Aurélien; Lepailleur, Alban; Rault, Sylvain
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>